Pengaruh Current Ratio (Cr) , Debt To Equity Ratio (Der) Dan Working Capital Turnover (Wcto) Terhadap Return On Asset (Roa) Pada Perusahaan Sub Sektor Otomotif Dan Komponen Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Tri Wahyudi; Juliani Lisma Sari; Windy Amalia Nur Fadilah; Ibnu Saepul Rohman (Departement of Mathematics Education, 2023)
This study aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Working Capital Turnover (WCTO) on Return On Assets in Automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The population of this study is automotive and component sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period as many as 60 company financial statements. The saturated sampling technique was used as a sampling technique and the 12 companies sampled in this study used quantitative and used associative approaches, using Regression and panels. Based on the results of partial research that Debt to equity ratio (DER), and Working Capital Turnover (WCTO) have no effect on Return On Assets. Simultaneously, Current Ratio (CR), Debt to Equty Ratio (DER), and Working Capital Turnover (WCTO) have a significant effect on Return On Assets.